Acúmulo de silício na parte aérea de cultivares de arroz de terras altas afetado pela aplicação de silicato e carbonato no solo - Mauad, Munir; Costa Crusciol, Carlos Alexandre [UNESP]; Nascente, Adriano Stephan; Grassi Filho, Hélio [UNESP]; Correa, Juliano Carulli (Universidade Estadual de Londrina (UEL), 2013)
Even the element silicon being the most uptake by rice plant, many benefit effect like: increase of pest and disease tolerance, decrease of lost of water by transpiration and better the leaf architecture becoming the leafs more erect, resulting as well at the better photosynthesis efficacy. There is not too much knowledge about the uptake march in upland rice plants. This study aimed to evaluate the content of silicon in two upland rice cultivars by the influence of the application of silicate and limestone at the soil. The experiment was carried in Hapludox soil in a completely randomized experimental design in 2x2x7 factorial scheme in four replications. The treatments were consisted of calcium silicate fertilizer and limestone in interaction with seven period of physiological stage, using the upland rice cultivars Caiapo and Maravilha. At the cultivar Maravilha Si accumulation begin from tillering and achieve it better value at the microsporogenesis, while the Caiapo cultivar, occurs between tillering until the mily grain. Caiapo shows efficient Si accumulation when it was supplied to the soil. Plant organs that more accumulated silicon in both upland rice cultivars followed decreased order: stem > leaf > panicle.
Silicon content in the shoots of upland rice cultivars as affected by the application of silicate and limestone in the soil
Keywords: Oryza sativa L.; physiologic stage; benefic element